Sorting machine using Ethernet automation system - Zulkarnain Shaharudin (Universiti Malaysia Perlis, 2008)
This project is to develop a distributed system with build a sorting machine using Ethernet automation system. Star topology is used in this system by dividing it into five stations for a complete system. Each station will be connected each other using Ethernet protocol (RJ45 socket and cable) and a hub. All the hardware in sorting machine including sensor, servo motor, stepper motor and pneumatic actuators must be connected to the Bus Terminal, all the hardware must be configured with TwinCAT System Manager software to make sure it can be synchronized with TwinCAT PLC Control software when programming this system. Next step is to design a program for each station and combine it into a main program. Ethernet that used in this system is a real time. The best way to test this system by measuring the execution time process with different factor like pressure. In this project, different pressure value between 40 PSI to 80 PSI was used to react with execution time. After finished the test, the optimum value is 80 PSI where this pressure execute the system in 36.1 seconds, the fastest execution time without any damage to the machine that cause by overload pressure. At 40 PSI, the execution time is 41.5 seconds, 5.4 seconds behind 80 PSI pressure execution time and some of the pneumatic actuators are not moving because of the low pressure. A few suggestions to upgrade this system in the future like develop interfacing software using Visual Basic language programming. This project is successful and all the system operates according to the program.